2019 32nd International Conference on VLSI Design and 2019 18th International Conference on Embedded Systems (VLSID) 2019
DOI: 10.1109/vlsid.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

EdgeCoolingMode: An Agent Based Thermal Management Mechanism for DVFS Enabled Heterogeneous MPSoCs

Abstract: Thermal cycling as well as temperature gradient in time and space affects the lifetime reliability and performance of heterogeneous multiprocessor systems-on-chips (MPSoCs). Conventional temperature management techniques are not intelligent enough to cater for performance, energy efficiency as well as operating temperature of the system. In this paper we propose a lightweight novel thermal management mechanism in the form of intelligent software agent, which monitors and regulates the operating temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…where l i : each frequency scaling level n : number of different frequency scaling level steps (6) Now, when the performance deadline is defined by the user in the P-EdgeCoolingModefor an executing application then from the operating frequency and achieved performance mapping deduced from Eq. 4 in the Learning module, the operating frequency, which is able to satisfy the defined performance deadline, is chosen from the mapping table instead of using the relationship deduced from Eq.…”
Section: Decision Modulementioning
confidence: 99%
See 3 more Smart Citations
“…where l i : each frequency scaling level n : number of different frequency scaling level steps (6) Now, when the performance deadline is defined by the user in the P-EdgeCoolingModefor an executing application then from the operating frequency and achieved performance mapping deduced from Eq. 4 in the Learning module, the operating frequency, which is able to satisfy the defined performance deadline, is chosen from the mapping table instead of using the relationship deduced from Eq.…”
Section: Decision Modulementioning
confidence: 99%
“…Whereas, Kirin 659 employs 4 ARM Cortex A-53 (big) CPUs and 4 ARM Cortex A-53 (LITTLE) CPUs and 2 ARM Mali-T830 GPU cores. Now a days most of the research and development in MPSoCs have been focused on developing algorithm to provide energy efficiency while catering for performance and reduced thermal gradient [3][4][5][6]. But in practical sense, majority of the published algorithms lack the flexibility for real world implementation because the usage and workload on similar devices by different users are different and hence, requires the resource management methodologies to be flexible to adapt over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study gave a novel approach on analyzing traffic using video cameras in low bandwidth network without the need to communicate the image frames over the WIFI network, the study also had energy consumption and device lifespan reliability issues (shown later in the section). Due to wide consumer adoption of mobile devices utilizing multi-processor system-on-a-chip (MPSoC) [26]- [28], which implements several different types of processing elements such as CPU/GPU on the platform, MPSoCs are perfect candidates for implementing computing resource demanding algorithms such as CNN based methodologies. When the CNN model proposed in the study [9] is implemented and trained on a MPSoC such as Odroid XU4 [29] (more on the hardware of Odroid XU4 in Sec.…”
Section: Introductionmentioning
confidence: 99%